Scaled 'LAMB'- performance with bitumen variation using MMLS testing and PPGS application - Smit, A. d F.(Andre de Fortier) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1995.